Augmenting Nutrient Acquisition Ranges of Greenhouse Grown CBD (Cannabidiol) Hemp (Cannabis sativa) Cultivars - Jennifer Kalinowski; Keith Edmisten; Jeanine Davis; Michelle McGinnis; Kristin Hicks; Paul Cockson; Patrick Veazie; Brian E. Whipker (Horticulturae, 2020)
There is a growing interest in the production of hemp for the extraction of cannabidiol (CBD) due to reported therapeutic benefits. Recent policy reform has permitted state hemp pilot programs, including the land grant research institutions, the ability to investigate the potential of growing and harvesting Cannabis sativa plants (≤0.3% tetrahydrocannabinol) for these purposes in the U.S. There are vast gaps of knowledge regarding the fertility requirements of hemp cultivars grown in a horticultural production setting for floral attributes such as the cannabinoid constituents. Foliar tissue analysis provides an avenue to determine adequate ranges for nutrient uptake and estimating fertilizer requirements prior to visual symptoms of deficiency or toxicity. To facilitate a survey range of elemental nutrient acquisition in hemp cultivars propagated for CBD production, foliar analysis was executed using the most recently mature leaves (MRML) of mother stock plants. All plants were maintained in the vegetative stage for twelve weeks, prior to initiation of cutting for clone harvesting. A total of thirteen cultivars were utilized to broaden previously reported baseline survey ranges. Significant differences were found among all thirteen cultivars in accumulation of both micro and macro essential nutrients, widening the range of the fertility requirements of Cannabis plants grown in this production model for CBD harvesting.